m6A Methylases Regulate Myoblast Proliferation, Apoptosis and Differentiation - Xinran Yang; Chugang Mei; Xinhao Ma; Jiawei Du; Jianfang Wang; Linsen Zan (Animals, 2022)
N6-methyladenosine (m6A) plays an important role in regulating gene expression. Previous studies found that m6A methylation affects skeletal muscle development. However, the effect of m6A methylases on bovine skeletal myogenesis is still unclear. Here, we found that the expression of m6A demethylases (FTO and ALKBH5) was significantly higher in the longissimus dorsi muscle of adult cattle than in newborn cattle. In contrast, the expression of m6A methyltransferases (METTL3, METTL14 and WTAP) was reduced. The mRNA expression of all five genes was found to be increased during the myogenesis of myoblasts in vitro. Knockdown of FTO or METTL3 promoted myoblast proliferation, inhibited myoblast apoptosis and suppressed myogenic differentiation, whereas ALKBH5 knockdown had the opposite effect. METTL14 knockdown enhanced myoblast proliferation and impaired myogenic differentiation. WTAP knockdown attenuated proliferation and contributed to apoptosis but did not affect differentiation. Furthermore, the functional domains of these five m6A methylases are conserved across species. Our results suggest that m6A methylases are involved in regulating skeletal muscle development and that there may be a complex network of m6A methylation regulating skeletal myogenesis.